The Impact of Peatland Damage and Its Influence on Food Security Policy in Sungai Apit Sub-District in 2023 - Albintani Muchid; Susanto Agus; Zebua Ben Hansel Notatema; Wasillah Asiah; Harirah Zulfa (E3S Web of Conferences)
The deterioration of peatlands will have a considerable impact on food security, which is of strategic importance with regard to social resilience, economic stability, political stability, national resilience, and national independence. This research project has the following objectives: (1) to identify food security policies and peat management policies in the Sungai Apit District; (2) to analyze the impact of peatland damage on food sustainability in the Sungai Apit District; and (3) to analyze the relationship between food security policies and peat management in the Sungai Apit District. This research employs the “Triple Helix” theory, as proposed by Etzkowitz and Leydersdorff (1995). The triple helix model is a qualitative research method that describes social behavior in society aimed at creating cooperative synergies between three key actors: academia (A), business (B), and government (G). The findings of this study indicate that the degradation of peatlands in Sungai Apit District has a detrimental impact on agricultural productivity, the incidence of environmental disasters, the quality of water sources, soil degradation, biodiversity loss, climate change, and socio-economic consequences. By implementing a triple helix collaboration policy, it is possible to achieve food sovereignty, which entails engaging the academic, business, and government sectors, particularly to enhance the accessibility, affordability, consumption, and nutritional value of food in Sungai Apit District.